2004
DOI: 10.1093/jpepsy/jsh064
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Evaluation of an Interactive Intervention Designed to Reduce Pediatric Distress During Radiation Therapy Procedures

Abstract: The interactive intervention was effective at reducing RT-related distress (as measured by HR) and would be a useful tool in pediatric radiation oncology settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 15 publications
1
38
1
1
Order By: Relevance
“…Techniques such as modeling, distraction, desensitization, positive reinforcement, relaxation, visual imagery, practice, education, and so forth have been found to significantly reduce RT-related distress. 4,31 Klosky et al, 31 for example, report on a randomized clinical trial that evidenced the efficacy of a cognitive-behavioral intervention in reducing RT-related distress similar to that of orally administered diazepam (Valium) among preschool-and school-aged children. 36 In a smaller study, Slifer 2 reports that Յ82% of pediatric patients between the ages of 2 and 7 years were able to complete RT simulation and treatment successfully without any use of sedation after completing a behavioral intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques such as modeling, distraction, desensitization, positive reinforcement, relaxation, visual imagery, practice, education, and so forth have been found to significantly reduce RT-related distress. 4,31 Klosky et al, 31 for example, report on a randomized clinical trial that evidenced the efficacy of a cognitive-behavioral intervention in reducing RT-related distress similar to that of orally administered diazepam (Valium) among preschool-and school-aged children. 36 In a smaller study, Slifer 2 reports that Յ82% of pediatric patients between the ages of 2 and 7 years were able to complete RT simulation and treatment successfully without any use of sedation after completing a behavioral intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The details and findings of this larger study are reported elsewhere. 31 Eligible patients were those who had a primary diagnosis of malignancy, aged 2 to 7 years at the time of RT simulation, used English as their primary language, had no previous experience with external beam irradiation, and were functioning at a level at which they could tolerate RT intervention. Accordingly, eligible patients were required to have an Eastern Cooperative Oncology Group (ECOG) performance status rating of 0 (no physical debilitation or functional impairment) to 3 (moderate physical debilitation or functional impairment) as reported by the child's physician.…”
Section: Participantsmentioning
confidence: 99%
“…Median age at diagnosis was 4.8 (2.7-8.1) years; 19 were male and 25 lived in cities. Median interview length was 16 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) min. Malignancies were leukemias (18), neuronal (six) and non-neuronal (three) solid tumors, and lymphomas (two).…”
Section: Broad Overview Of Participantsmentioning
confidence: 99%
“…Parental beliefs about music's effects on pediatric oncology outpatients indicated improved relaxation, but, paradoxically, the children presented with increased sympathetic activity based on heart rate variability analysis [17]. Other helpful supportive modalities used with young cancer patients include self-selected distracters with port access or venipuncture [18], art therapy with bone aspirations and lumber punctures [19], and an interactive cartoon figure [20], play preparation [21], and behavioral training [22] interventions with radiotherapy.…”
mentioning
confidence: 99%
“…Deste modo, torna-se necessário a construção e uso de métodos de avaliação e de estratégias de intervenção que reduzam o sofrimento da criança, atuando na prevenção das reações de dor e da ansiedade em procedimentos seguintes (Dahlquist, Pendley, Landthrip, Jones & Steuber, 2002;Dahlquist, McKenna, Jones, Dillinger, Weiss & Ackerman, 2007;Klosky, Tyc, Srivastava, Tong, Kronenberg, Booker & Merchant, 2004;Manne, Bakeman, Jacobsen, Gorfinkle & Redd, 1994;Manne, Redd, Jacobsen, Gorfinkle, Schorr & Rapkin, 1990 Além das crianças, os adolescentes também foram avaliados em um estudo sobre o enfrentamento das situações de estresse relacionadas à diabetes tipo 1 (Jaser & White, 2011).…”
Section: Adoecimento E Hospitalização: a Criança E A Famíliaunclassified